Philosophy 167: Class 8 - Part 7 - Two Hard Cases for Mechanical Philosophy- Descartes' Accounts of Magnetism and Gravity. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Review of Descartes' accounts for magnetism and gravity.; Opening line: "Obviously, a terrible difficulty facing the mechanical philosophy was magnetism."; Duration: 7:20 minutes.; Segment: Class 8, Part 7.